Managing reality managing the contract - Mitchell, Bronwyn (Institution of Civil Engineers (ICE), 2005)
Managing Reality Book 3 Managing the Contract is essentially for those who use the contract on a daily basis, covering the detail of practical management such as paying the contractor, reviewing the programme, ensuring the quality of the works and dispute resolution. Both first-time and experienced practitioners will benefit from this book.